2005
DOI: 10.1152/japplphysiol.01029.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone treatment in the newborn rat: fatty acid profiling of lung, brain, and serum lipids

Abstract: treatment in the newborn rat: fatty acid profiling of lung, brain, and serum lipids. J Appl Physiol 98: [981][982][983][984][985][986][987][988][989][990] 2005. First published November 12, 2004; doi:10.1152/japplphysiol.01029.2004.-Dexamethasone is used as treatment for a variety of neonatal syndromes, including respiratory distress. The present study utilized the power of comprehensive lipid profiling to characterize changes in lipid metabolism in the neonatal lung and brain associated with dexamethasone tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…We have also demonstrated that ghrelin, a hormone released by the GI tract that has a wide variety of endocrine and metabolic actions, is increased by dexamethasone therapy ( 15 ). The differential actions of leptin and ghrelin on food intake, insulin sensitivity, and metabolic function made it clear that these two factors per se could not account for the changes in growth hormone ( 7 ), IGF-I ( 8 ), body composition ( 7,8 ), weight gain ( 7,8 ), lipid profiles ( 12,14 ), and other parameters of metabolic function in our previous studies.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have also demonstrated that ghrelin, a hormone released by the GI tract that has a wide variety of endocrine and metabolic actions, is increased by dexamethasone therapy ( 15 ). The differential actions of leptin and ghrelin on food intake, insulin sensitivity, and metabolic function made it clear that these two factors per se could not account for the changes in growth hormone ( 7 ), IGF-I ( 8 ), body composition ( 7,8 ), weight gain ( 7,8 ), lipid profiles ( 12,14 ), and other parameters of metabolic function in our previous studies.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, we have recently demonstrated that a tapering regimen of the glucocorticoid dexamethasone, administered to mimic clinical practice ( 11 ), results in hyperinsulinemia with normoglycemia and decreased weight gain ( 12 ). There is also a significant interaction between dexamethasone, which is often used to treat neonatal cardiopulmonary disorders ( 13 ), and hypoxia with respect to many parameters of metabolic function ( 12,14,15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dexamethasone exerts a series of effects on injured neural tissue (13,20). These effects are the regulation of energy metabolism, the prevention of progressive posttraumatic ischemia, the prevention of neurofilament degradation and the inhibition of membrane lipid hydrolysis (3,4,25). Thus, it has been long believed that, with dexamethasone treatment, the structural and functional integrity of biological membranes can be preserved (3,15).…”
Section: Discussionmentioning
confidence: 99%
“…These effects are the regulation of energy metabolism, the prevention of progressive posttraumatic ischemia, the prevention of neurofilament degradation and the inhibition of membrane lipid hydrolysis (3,4,25). Thus, it has been long believed that, with dexamethasone treatment, the structural and functional integrity of biological membranes can be preserved (3,15). The primary mechanism of the neuroprotective effect of dexamethasone is the inhibition of lipid peroxidation (4,5,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation